Staple versus Suture Closure for Ankle Fracture Fixation: Safety and Outcomes. Issue 3 (14th September 2018) - Shah, Ashish; Lehtonen, Eva; Patel, Harshadkumar; Pinto, Martim; Phillips, Sierra; Naranje, Sameer; Pitts, Charles; Kalra, Rishi; Huntley, Samuel
Category: Trauma Introduction/Purpose: Ankle fractures are commonly treated fractures by orthopaedic surgeons with unique challenges to skin closure due to the lack of subcutaneous support. Metallic staples are a commonly accepted method of skin closure in other specialties, though the use of staples in orthopaedics, and more specifically in foot and ankle surgery, remains a topic of debate. Proponents of staples report several potential advantages to using staples instead of sutures, including reduced closure time, faster and less painful removal, or improved cosmetic appearance. This study aimed to compare outcomes of suture versus staple closure as well as to evaluate the safety of staple closure after open fixation of acute traumatic ankle fractures. Methods: The medical records of 94 patients treated at our institution with open fixation of an acute traumatic ankle fracture by a single surgeon between January 2011 and June 2017 were retrospectively reviewed. Demographics, preoperative characteristics, relevant comorbidities, operative characteristics, and postoperative outcomes were compared between patients who received superficial skin closure using staples versus suture techniques. Statistical analysis was performed using chi-squared test and Fisher's exact test. Results: The staple and suture group patients were demographically similar at baseline. Of the 94 patients included in this study, 10 patients developed local wound related complications postoperatively, including 5 with wound dehiscence, 4 with superficial wound infections, and 1 deep infection . Eight patients required revision surgery due to infection or wound dehiscence. Four patients in the suture group developed superficial wound infections, compared with zero in the staple group. One patient in the staple group developed a deep infection. With the numbers available, no significant differences could be detected in the incidence of postoperative infections, local wound related complications and revision surgeries between two wound closure groups. Conclusion: Our data suggests that there is no statistical difference in outcomes between staple and suture closure after open fixation of acute ankle fractures. Because there was no difference in morbidity with possible benefits of reduced closure time, faster removal, and improved cosmetic appearance, we conclude that staple closure may be a safe alternative to sutures for superficial skin closure. This study adds evidence to a growing body of literature and suggests that staples can be used in some instances, clinical decision making, surgeon preference, and technique proficiency should remain the cornerstone of closure in ankle fracture surgery.